Effects of modified hybrid resistance training on concentric quadriceps femoris peak torque and eccentric hamstring peak torque in untrained healthy subjects - Priyantono, Wirawan Indra; Tinduh, Damayanti; Prawitri, Yudith Dian; Pawana, I Putu Alit; Melaniani, Soenarnatalina (Bali medical journal, 2023)
Background: Leg muscular strength may decline as a result of decreased mechanical stress on the muscles brought on by the COVID-19 pandemic's physical inactivity. The hybrid training method uses the force generated by an electrically stimulated antagonist muscle to resist a voluntarily contracting agonist muscle. Due to the lack of external resistance or stability equipment, this exercise may be a good option for strengthening workouts during a pandemic. Modifications were made using conventional stimulation tools because the hybrid training system was difficult to replicate. The study's objective was to analyze the effect of modified hybrid resistance training on concentric quadriceps femoris peak torque (QCON) and eccentric hamstring peak torque (HECC). Methods: The study was conducted at the Medical Rehabilitation Installation of Dr. Soetomo General Academic Hospital Surabaya. The subjects were 30 untrained healthy men aged 18-40 years divided into the treatment group, which received modified hybrid resistance training and the control group, which received Russian protocol neuromuscular electrical stimulation 3 times per week for 4 weeks. Due to COVID-19 infection, four participants couldn’t continue in intervention. Statistical tests were carried out on subjects that were able to complete the study (treatment: 13, control:13). Results: There were increases in 60o/sec QCON (p-value 0.005) and 120o/sec QCON (p-value 0.001) in the non-dominant leg in the treatment group. There were increases in 60o/sec QCON (p-value 0.043), 120o/sec QCON (p-value 0.014), and 120o/sec HECC (p-value 0.043) in the non-dominant leg in the control group. There is a significant difference in non-dominant 120o/sec ΔQCON between the two groups (p-value 0.036). Conclusion: There was a more significant increase in QCON in the modified hybrid training exercises group compared to the Russian stimulation group in untrained healthy subjects.